ORGANIZATION OF GASIFICATION OF THE REPUBLIC OF CRIMEA - O. V. Baikova; A. O. Sumenkov (Вестник университета)
The problems of gasification of the population of the Republic of Crimea have been considered. It has been revealed, that the lack of gas in the settlements of the Republic hinders the development of social infrastructure, as gas fuel provides significant saving money for consumers. The priority aspects of gasification in the regions and in the Republic of Crimea have been listed. The conditions of priority allocation of investments for gasification of the region have been named. Solutions to the problems between the regional government and business representatives have been offered. The existing examples of gasification have been adduced.